2006
DOI: 10.1016/j.avb.2005.09.001
|View full text |Cite
|
Sign up to set email alerts
|

Aggression and brain asymmetries: A theoretical review

Abstract: The relationship between aggression and brain asymmetries has not been studied enough. The association between both concepts can be approached from two different perspectives. One perspective points to brain asymmetries underlying the emotion of anger and consequently aggression in normal people. Another one is concerned with the existence of brain asymmetries in aggressive people (e.g., in the case of suicides or psychopathies). Research on emotional processing points out the confusion between emotional valen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
13
0
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 91 publications
2
13
0
1
Order By: Relevance
“…loss of mother and allomothers, premature weaning, witness to family deaths, herd dissolution, translocation; ) during periods when critical patterning of brain development occurs (Schore 2003a). Neurobiologically, their hyper-aggression is consistent with an intense state of amygdala-hypothalamic sympathetic hyperarousal and a weakened higher right orbitofrontal inhibitory system associated with impaired developmental trauma (Rohlfs & Ramirez 2006). The absence of second phase all-male socialization is also likely to have been a significant factor leading to affective dysregulation.…”
Section: Neuroethology Of Elephant Atypical Behaviourmentioning
confidence: 84%
See 2 more Smart Citations
“…loss of mother and allomothers, premature weaning, witness to family deaths, herd dissolution, translocation; ) during periods when critical patterning of brain development occurs (Schore 2003a). Neurobiologically, their hyper-aggression is consistent with an intense state of amygdala-hypothalamic sympathetic hyperarousal and a weakened higher right orbitofrontal inhibitory system associated with impaired developmental trauma (Rohlfs & Ramirez 2006). The absence of second phase all-male socialization is also likely to have been a significant factor leading to affective dysregulation.…”
Section: Neuroethology Of Elephant Atypical Behaviourmentioning
confidence: 84%
“…2001) during periods when critical patterning of brain development occurs (Schore 2003a). Neurobiologically, their hyper‐aggression is consistent with an intense state of amygdala–hypothalamic sympathetic hyperarousal and a weakened higher right orbitofrontal inhibitory system associated with impaired developmental trauma (Rohlfs & Ramirez 2006).…”
Section: Neuroethology Of Elephant Atypical Behaviourmentioning
confidence: 99%
See 1 more Smart Citation
“…These differences between hierarchical statuses were assumed to be the consequence of higher levels of psychosocial stress (e.g., competition for access to food and space) experienced by subordinates leading to greater right‐hand use. The possibility that stress could elicit a right‐side bias at the population level is supported by several studies (chimpanzees: Prieur et al, ; Prieur et al, ; gorillas: Prieur, Pika, Barbu, & Blois‐Heulin, ; rats: e.g., Alonso, Castellano, & Rodriguez, ; Castellano, Diaz‐Palarea, Barroso, & Rodriguez, ; Castellano, Diaz‐Palarea, Rodriguez, & Barroso, ; anoles: Deckel, ; see also Rohlfs & Ramirez, for review of reports on humans). According to Barnard, Matthews, Messori, Podaliri‐Vulpiani, and Ferri (), stress due to partial separation would be linked to strength of ewes’ and their lambs’ laterality.…”
Section: Non‐human Primates’ Manual Laterality For Manipulations and mentioning
confidence: 91%
“…A recent study sought to assess this construct by using Gray's Behavioural Inhibition/Behavioural Activation scale [15], but had to remove the measure from analysis due to problems with internal consistency [19]. While other recent studies have utilized the BIS/BAS scales and have found support for the hypothesized relationship between a temperament such as behavioural inhibition and violent behaviour [34,35], future studies will have to carefully choose an appropriate measurement tool for assessing this important construct in concert with emotion regulation and other relevant variables before support for its place in the AAM can be stated. Until then, little can be said beyond the theoretical proposition.…”
Section: Introductionmentioning
confidence: 99%